Pan‐cancer analysis shapes the understanding of cancer biology and medicine - Xiaoping Cen; Yuanyuan Lan; Jiansheng Zou; Ruilin Chen; Can Hu; Yahan Tong; Chen Zhang; Jingyue Chen; Yuanmei Wang; Run Zhou; Weiwei He; Tianyu Lu; et al. (Cancer Communications)
Abstract Advances in multi‐omics datasets and analytical methods have revolutionized cancer research, offering a comprehensive, pan‐cancer perspective. Pan‐cancer studies identify shared mechanisms and unique traits across different cancer types, which are reshaping diagnostic and treatment strategies. However, continued innovation is required to refine these approaches and deepen our understanding of cancer biology and medicine. This review summarized key findings from pan‐cancer research and  explored their potential to drive future advancements in oncology.